Pedagogi Feminis sebagai Framework : Menelusuri Upaya dan Strategi Pencegahan Kekerasan Seksual di Perguruan Tinggi - Amaliatulwalidain, Amaliatulwalidain; Putra Anwar Ginting, M. Alief Akhbar; Melinda, Melinda (Jurnal Pemerintahan dan Politik, 2024)
This article aims to provide a form of sexual violence prevention strategy based on feminist pedagogy as a framework for the PPKS Task Force in universities. It is known that the main factor in the rampant cases of sexual violence in several universities in Indonesia is basically caused by the imbalance of power relations in unbalanced gender positions, a culture of masculine oppression, including the lack of literacy in understanding knowledge about gender equality so that its linearity has an impact on various forms of sexual violence that occur. The theoretical approach used in this study uses the theory of feminist pedagogy, while the methodology used in this study is qualitative-reflective through literature studies from learning data and observations on the existence and role of the PPKS Task Force in Palembang City, including the PPKS Task Force at Sriwijaya University and the PPKS Task Force at Indo Global Mandiri University. The results of the study show that the prevention of sexual violence carried out by the two PPKS Task Forces at the two universities plays a role in two indicators, namely First, self-reflection and the PPKS Task Force's partisanship on feminist issues. Second, Empowerment of collaborative communities by involving academics through the formation of anti-sexual violence solidarity, namely "Volunteer Satgas PPKS" and "Sister bootcamp" while the transformative social role has not been fully constructive, because there has been no integration of alternative feminist-based curriculum as comprehensive and systematic sexual violence learning in preventing sexual violence in higher education.